Respuesta :

The result of the expression -(3)⁰.⁵x for x = -2 is 3.4, for x = 0 is 0 and for x = 2 is - 3.4

The question states to evaluate the given expression, that is, -(3) ⁰.⁵ x for the given values of x, that are, x = -2, x = 0, and x = 2.

This question can be easily solved by using the concept of substitution. We have to substitute the given values of x in the given expression one after the other and note the answer.

For x = -2.

we get, -(3) ⁰.⁵ ( - 2) = - 1.7 * (-2) = 3.4

For x = 0.

we get, -(3) ⁰.⁵ ( 0 ) = - 1.7 * ( 0 ) = 0

For x = 2.

we get, -(3) ⁰.⁵ ( 2 ) = - 1.7 * ( 2 ) = - 3.4

Therefore, we get the result of the expression -(3)⁰.⁵ x for x = -2 as 3.4, for x = 0 as 0 and for x = 2 as - 3.4

Learn more about Substitution here:

https://brainly.com/question/16609931?referrer=searchResults

#SPJ9